Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan Fintech pada UMKM di Kota Batam - Tamara Raini Indah; Erni Yanti Natalia (Economic Reviews Journal, 2026)
The development of digital technology has driven significant changes in the financial sector through financial technology (fintech), which offers convenience, efficiency, and broader access to financial services, particularly for culinary micro, small, and medium enterprises (MSMEs). However, fintech utilization among MSMEs in Indonesia, including Batam City, remains suboptimal, indicating the influence of various factors. This study aims to analyze the effects of perceived ease of use, perceived usefulness, perceived risk, and trust on fintech usage intention among MSMEs in Batam City. A quantitative approach with a survey method was employed, involving 95 culinary MSMEs selected through random sampling. Data were analyzed using multiple linear regression. The results show that perceived ease of use, perceived usefulness, and perceived risk have a positive and significant effect on fintech usage intention, while trust has a negative effect. Simultaneously, all variables significantly influence fintech usage intention.